Philosophy of nature: physiology - Allow, Ahmed Kaid Naji; El Sersi, Magdi (IIUM Press, International Islamic University Malaysia, 2018)
Physiology is a science that deals with the functions of different tissues and organs in the living body. The human body is much more than the sum of its parts. Life relies upon this total function, not just on the function of individual parts of the body in isolation, but with other parts. The word physiology was first used by the Greeks around 600 BC to describe a philosophical inquiry into the nature of things. Thus early physiologists were philosophers and they explained that physiology is the philosophy of nature based on their perception. So we can postulate that the legal daughter of philosophy is physiology. In the past to be a good doctor or social health-worker or medical-physiologist, you had also to be a good philosopher as physiology tries to answer the most difficult questions in our life. For example: what is life? How is it sustained? Why is life such and such? As many as 106 times the Nobel Prize in medicine had been awarded to physiologists. In this chapter we are going to explain the successful way to understand human physiology, How to think like physiologist, what are the tools that can help to understand physiology. By the end, what are the applicable references for study physiology. All these questions, we are trying to explain it in this chapter.